Effective adsorption of crystal violet from aqueous solutions with effective adsorbent: equilibrium, mechanism studies and modeling analysis. Issue 1 (1st January 2021) - AL-Shehri, Hamza S.; Almudaifer, Eyad; Alorabi, Ali Q.; Alanazi, Hamdah S.; Alkorbi, Ali S.; Alharthi, Fahad A.
ABSTRACT: In this work, NaOH-activated Aerva javanica leaf (NAJL) powder was successfully developed as a cost-effective adsorbent for removal of crystal violet (CV) from an aqueous environment. The prepared adsorbent was characterized using FTIR, SEM, and their surface area was determined by BET technique. Different parameters affecting the adsorption of CV dye such as pH solution, adsorbent dose, equilibrium time, initial CV concentration, and temperature were investigated. The results revealed that the best-optimized values were found as pH–9, dose–20 mg, time–30 min, temperature– 25 ° C. The adsorption experimental data exhibited excellently fitted well to the nonlinear Langmuir isotherm and Pseudo-first-order kinetic models. The maximum monolayer adsorption capacity of CV dye was 315.2 mg/g. The experimental parameters of thermodynamic analysis exhibited that the CV dye adsorption onto NAJL powder was exothermic and spontaneous. Electrostatic attraction, π-π interactions, and Hydrogen bonding were the mechanism behind the adsorption of CV dye.